Pengelolaan Food Waste Tingkat Rumah Tangga bagi Kader PKK di Desa Sumput Kabupaten Sidoarjo - Wedowati, Endang Retno; Rejeki, Fungki Sri; Puspitasari, Diana; Handarini, Kejora; Rahmiati, Retnani (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service aims to improve the knowledge and skills of PKK cadres in managing food waste bg processing it into useful products. The implementation method of this community service used counseling and training in processing pineapple skin waste into fermented drinks. The target partners were PKK cadres in Sumput Village, Sidoarjo Regency. The activity evaluation instrument used a questionnaire with a data analysis technique, namely descriptive analysis through frequency testing. The results of this community service showed an increase in partner knowledge and insight regarding food waste and its management, this is indicated by changes in community behavior to be more concerned about the use of food ingredients. In addition, there was a transfer of technology to target partners regarding the processing of pineapple skin waste into fermented drinks.